Power Balance Estimation in Long Duration Discharges on QUEST. (November 2016) - Hanada, K.; Zushi, H.; Idei, H.; Nakamura, K.; Ishiguro, M.; Tashima, S.; Kalinnikova, E. I.; Nagashima, Y.; Hasegawa, M.; Fujisawa, A.; Higashijima, A.; Kawasaki, S.; et al.
Abstract: Fully non-inductive plasma start-up was successfully achieved by using a well-controlled microwave source on the spherical tokamak, QUEST. Non-inductive plasmas were maintained for approximately 3–5 min, during which time power balance estimates could be achieved by monitoring wall and cooling-water temperatures. Approximately 70%–90% of the injected power could be accounted for by calorimetric measurements and approximately half of the injected power was found to be deposited on the vessel wall, which is slightly dependent on the magnetic configuration. The power distribution to water-cooled limiters, which are expected to be exposed to local heat loads, depends significantly on the magnetic configuration, however some of the deposited power is due to energetic electrons, which have large poloidal orbits and are likely to be deposited on the plasma facing components.